Optimasi Desain Geometri Lereng Material Old Dump Pada Usaha Penggalian Ulang Pit X PT. Bukit Asam Tbk - Rosihan Pebrianto; Anna Amelia Louisa; Edwin Harsiga; Harry Waristian (MINERAL, 2024)
In doing slope design, it is necessary to pay attention to slope geometry and soil shear strength. Determination of slope geometry design also considers the balance between height and slope and production benefits. Research was conducted to analyze slope stability through physical and mechanical properties testing, limit equilibrium, and probabilistic Monte Carlo methods. The surface area of the Overburden stripping area in the 2024 RKP design is 8,172.79 m2. The production target is 2,000,000 tons of coal with a volume of overburden material that must be stripped of 29,000,000 BCM and obtained a Stripping Ratio value of 14.5. The results of the evaluation of the overall slope of the Old Dump material with an overall slope height of 66.582 m, a slope width of 447.69 m, an overall slope of 8.32˚ and a bench width of 25 m, a bench height of 6 m with a comparison ratio of 1:3 and a single slope angle of 18.43˚. Then the redesign was carried out and obtained recommendation results of 64.799 m overall slope height, 303.33 m slope width, 13.02˚ overall slope, and 25 m bench width, bench height at elevation 131-110 of 8 m with a comparison ratio of 1:2, single slope 26.57˚ and at elevation 110-50 of 8 m with a comparison ratio of 1:1.5, single slope 33.69˚.